Synthesis Characterization and Biological Investigations on Metal Complexes of 2-[(8-Hydroxy-1-quinolin-5-yl) methyl]-1H-isoindole-1, 3 (2H) dione - M. R. Solanki; G. D. Acharya; M. V. Hathi (E-Journal of Chemistry)
The more significant biologically active Cu(II), Ni(II), Co(II) and Mn(II) complex were synthesized by using N-hydroxymethyl phthalimide and 8-hydroxy quinoline as ligand. Synthesized complexes were characterized by elemental analysis, conductance, magnetic susceptibility measurements, IR and reflectance spectral studies. Coordination of the ligand atom to the metal ion was deduced by IR and reflecting spectral data. Structures of the complexes were confirmed by magnetic studies. All the complexes have been screened for antibacterial and antifungal.